What Drives Avoskin Consumers' Purchase Intention? Examining the Roles of Green Brand Image, Environmental Knowledge, and Green Trust - Umi Nur Nadzifah; Nawari Nawari; Ariefah Sundari (JURNAL ECONOMINA, 2026)
Growing public interest in ecological conservation has triggered a massive surge in demand for sustainable cosmetics, forcing skincare brands to implement eco-friendly marketing. However, buying decisions for sustainable skincare depend on tricky psychological dynamics, including green trust, eco-brand perception, and environmental literacy. This research explores how green brand image and ecological knowledge shape purchase intention, utilizing green trust as a mediator. Focusing on Indonesian Avoskin users, this causal quantitative study gathered empirical data from 96 respondents through a purposive online survey. Data processing was conducted via SmartPLS 4 under the PLS-SEM framework. The results indicate that green trust and environmental awareness heavily dictate consumer purchase willingness. Conversely, a green brand image fails to trigger a direct impact on buying intentions. Furthermore, both brand reputation and ecological literacy play a vital role in fostering consumer trust. Mediation analysis confirms that green trust successfully links environmental knowledge to final buying intentions, yet it cannot bridge the path from green brand image to purchase intention. These outcomes imply that boosting consumer ecological literacy and ensuring authentic green branding are the main keys to converting sustainable values into real purchases.